The Coffeehouse Investor's Ground Rules - Schultheis, Bill (Ascent Audio, 2021)
Building off the framework of Schultheis's The Coffeehouse Investor philosophy, this book will instill the common man and woman with the confidence to take control over their long-term financial goals and journey towards financial freedom in retirement. The Coffeehouse Investor's Ground Rules encourages listeners to ignore stock market "rules" and "perfect portfolio" pursuits to focus on the only three essential components to long-term financial security: saving, investing, and planning. Each component will be further broken down and explained through topics such as: - How to save money with confidence - The benefit of saving a little - Why women should invest in their financial destiny - The problem with underestimating your own financial abilities